QOL-38. USE OF COMPUTERIZED NEUROPSYCHOLOGICAL MEASURES TO ASSESS COGNITIVE MORBIDITY IN SURVIVORS OF CHILDHOOD BRAIN TUMORS. (4th December 2020) - Dickson, Duncan; Channell, Jessica; Mettetal, Ashley; Chick, Elizabeth; Wilkening, Greta; Liu, Arthur; Hankinson, Todd; Foreman, Nicholas; Hutaff-Lee, Christa
Abstract: Treatment of central nervous system (CNS) tumors in pediatric populations is associated with significant cognitive morbidity. Documentation of neuropsychological deficits is vital to treatment and educational planning. We investigated the feasibility and utility of a computerized neuropsychological measure (NIH Toolbox Cognitive Battery) in differentiating individuals who received tumor treatment from healthy controls. Participants included pediatric CNS tumor survivors (N = 85; Mean Age = 13.47; SD = 4.76) at least 1-year post-completion of treatment and healthy sibling controls (N = 20; Mean Age = 10.2; SD = 3.21) who completed the NIH Toolbox. Ninety-eight percent of the participants enrolled completed the computerized tasks. The overall logistical regression model, with NIH Toolbox tests as predictors, was statistically significant [χ2 (7, N = 105) = 26.176; p < .001] and improved correct group classification from 81% to 82.9%. Picture Sequencing (β = -0.059; Wald = 6.942; p = .008) and Flanker (β = -0.083; Wald = 7.473; p = .006) were both statistically significant and negatively predictive of membership in the treatment group. For each 1 unit increase in standard score on measures of working memory and inhibition, odds of membership in the treatment group decreased by 6.2% and 8.7%, respectively. Consistent with the literature, worse performance on computerized measures of cognitive functioning mediated by executive functioning was correlated with a history of brain tumor treatment. Further investigation will focus on comparing computerized neuropsychological tools to traditional comprehensive neuropsychological evaluations and clarifying the trajectory of these deficits across recovery.